Preparation method of a fluorescent probe for plasma enhanced fluorescence and its application in ellagic acid detection

The gold nanoparticle structure-enhanced silicon point fluorescence probe prepared by plasma enhanced fluorescence technology solves the problems of complex operation and expensive instruments in ellagic acid detection, and realizes the rapid and highly sensitive detection of ellagic acid, which has high specificity and Stability, suitable for large-scale production.

CN117186882BActive Publication Date: 2024-12-27NANJING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310575777.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-19
Publication Date
2024-12-27
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

The existing ellagic acid detection methods are complex in operation, expensive instruments or severe environmental interference, and lack convenient, efficient, high sensitivity and low cost detection methods.

Method used

A silicon dot fluorescent probe based on the structure enhancement of gold nanoparticles is prepared by plasma-enhanced fluorescence technology. The gold nanoparticles and blue-emitting silicon quantum dots are coated with silica as plasma-enhanced fluorescent substances, and the surface is carried out 3. -Aminobenzene boric acid modification to form a specific ellagic acid indicator.

Benefits of technology

The specific, fast and highly sensitive fluorescence detection of ellagic acid is achieved, with a detection time of about 5 minutes and a linear range of 0.5-100μM. It has high specificity and stability, low cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117186882B_ABST
    Figure CN117186882B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a fluorescent probe of plasma enhanced fluorescence and its application in ellagic acid detection, wherein anhydrous ethanol, TEOS and ammonia are reacted in a gold nanoparticle solution to obtain silicon dioxide gold nanoparticles, and reacted with APTMS to obtain amino-modified silicon dioxide-wrapped gold nanoparticles; sodium citrate, 3-APTES and glycerol are reacted to obtain a silicon dot solution, citric acid, EDC and NHS are added to form citric acid-modified silicon dots, and then reacted with EDC, NHS and amino-modified silicon dioxide-wrapped gold nanoparticle solution to obtain a silicon dot-modified gold nanoparticle solution on the surface of silicon dioxide; 3-aminophenylboronic acid, EDC and NHS are then added to react to obtain a fluorescent probe of plasma enhanced fluorescence. The fluorescent probe of plasma enhanced fluorescence prepared by the present invention has good stability, strong specificity and high sensitivity, and can be used for quantitative detection of ellagic acid and is more efficient, cost-saving and more accurate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plasma enhanced fluorescence, and in particular relates to a preparation method of a plasma enhanced fluorescence fluorescent probe and an application of the probe in ellagic acid detection. Background Art

[0002] Ellagic acid is a polyphenolic molecule that is widely found in many plants and fruits in nature. In terms of skin care, it can inhibit tyrosinase activity, block melanin production, and has whitening and spot-lightening effects. Ellagic acid has antioxidant, anti-cancer and anti-inflammatory properties, so it is used as a food additive or added to dietary supplements.

[0003] At present, the main detection methods for ellagic acid are chromatography, electrochemical detection and fluorescence detection. These methods often have the disadvantages of complex operation, expensive instruments or large environmental interference. With the development of the times, a more convenient, efficient, sensitive and low-cost detection method is sought to meet more stringent detection requirements. In recent years, fluorescent nanomaterials have aroused great interest due to their special optical properties. Quantum dots have received widespread attention in the fields of food safety, material analysis and determination, and biological cell imaging. Although quantum dots themselves have high quantum yields and fluorescence intensity in solution, in actual use, quantum dots are easily quenched after grafting with other substances. For this reason, a method for improving the fluorescence intensity and stability of quantum dots is proposed, namely, the plasma enhanced fluorescence effect. The enhancement or quenching effect depends on the distance between the metal particles and the fluorophore. When the fluorescent molecules are in direct contact with the metal nanoparticles, the fluorescence intensity is significantly quenched. However, when the fluorescent substance is at a certain distance from the plasma, the fluorescence of the fluorescent substance can be significantly enhanced. In addition, the application of plasma enhanced fluorescence probes to ellagic acid detection has not been reported. Summary of the invention

[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a method for preparing a fluorescent probe of plasma enhanced fluorescence. The fluorescent probe prepared by the present invention improves the luminescence intensity of silicon dots by plasma enhanced fluorescence technology, has an "on-off" characteristic dependent on ellagic acid concentration, and can be used as a specific ellagic acid concentration indicator. The probe prepared by the present invention can effectively solve the shortcomings of the existing ellagic acid detection, such as complicated operation, expensive instruments, or large environmental interference.

[0005] The invention also provides the prepared plasma enhanced fluorescence fluorescent probe and the application of the probe in ellagic acid detection.

[0006] Technical solution: In order to achieve the above-mentioned purpose, the method for preparing a fluorescent probe for plasma enhanced fluorescence described in the present invention comprises the following steps:

[0007] (1) adding sodium citrate to a chloroauric acid solution and heating the solution to produce a gold nanoparticle solution;

[0008] (2) reacting anhydrous ethanol, tetraethyl orthosilicate (TEOS) and ammonia water in a gold nanoparticle solution to obtain a gold nanoparticle solution coated with silica;

[0009] (3) reacting 3-aminopropyltrimethoxysilane (APTMS) with a solution of gold nanoparticles coated with silica to obtain a solution of gold nanoparticles coated with silica with surface modified amino groups;

[0010] (4) reacting sodium citrate, APTES and glycerol to obtain a silicon dot solution;

[0011] (5) reacting citric acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS) and the silicon dot solution to obtain a citric acid-modified silicon dot solution;

[0012] (6) reacting the citric acid-modified silicon dot solution, EDC, NHS and the surface-modified amino group-coated gold nanoparticle solution to obtain a silicon dot-modified gold nanoparticle solution on the surface of silicon dioxide;

[0013] (7) 3-Aminophenylboronic acid, EDC, NHS and a solution of gold nanoparticles modified with silicon dots on the surface of silica were reacted to obtain a fluorescent probe with plasmon-enhanced fluorescence.

[0014] In step (1), the chloroauric acid aqueous solution is heated to boiling, a sodium citrate solution is added for reaction, the solution is allowed to continue boiling for 3-7 minutes after turning into wine red, and then the heating is turned off to obtain a gold nanoparticle (Au NPs) solution, and the solution is observed to turn from colorless to wine red; the mass ratio of the chloroauric acid to the sodium citrate is 1:1-10.

[0015] Preferably, the sodium citrate is sodium citrate with a mass fraction of 1%, and the mass ratio of chloroauric acid to sodium citrate in step (1) is 1:1.

[0016] Furthermore, the heating and boiling to obtain the gold nanoparticles in step (1) is maintained under boiling conditions for 5 minutes.

[0017] In step (2), anhydrous ethanol and ammonia water are added to the gold nanoparticle solution, and then TEOS solution is added to continue the reaction for 6-24 hours to obtain a silica-encapsulated gold nanoparticle (Au NPs@SiO2) solution; the volume ratio of the gold nanoparticle solution, anhydrous ethanol, ammonia water and TEOS is 100:150-800:3-10:7-15.

[0018] Preferably, TEOS is added in step (2) and the reaction is continued for 12 hours, wherein the volume ratio of the Au NPs solution, anhydrous ethanol, ammonia water and TEOS is 100:200:7:11.

[0019] In step (3), APTMS and a solution of gold nanoparticles coated with silica are reacted at 30-40° C. for 3-7 hours, and then reacted at 40-60° C. for 1-2 hours to obtain an amino-modified solution of gold nanoparticles coated with silica (Au NPs@SiO2-NH2); the volume ratio of the APTMS to the solution of gold nanoparticles coated with silica is 1-2:10.

[0020] Preferably, in step (3), APTMS and Au NPs@SiO2 solution are reacted at 37° C. for 5 h, and then at 50° C. for 1 h. The volume ratio of APTMS to AuNPs@SiO2 is 1:10.

[0021] In step (4), 0.2-0.4 g sodium citrate and 8 mL glycerol are reacted at room temperature for 20-40 min, then APTES is added and the reaction is continued for 5-15 min, and then the reaction is carried out at 170-190° C. for 1-2 h to obtain a silicon dot (Si QDs) solution; the volume ratio of glycerol to APTES is 8:1-2.

[0022] Preferably, in step (4), 0.318 g of sodium citrate and 8 mL of glycerol are reacted at room temperature for 20 min, then APTES is added and the reaction is continued for 10 min, and then the reaction is carried out at 185° C. for 1.5 h. The volume ratio of glycerol to APTES is 8:2.

[0023] In step (5), citric acid, EDC and NHS are dissolved in ultrapure water, and then silicon dot solution (0.05-0.2 mL diluted to 1-2 mL) is added and reacted at room temperature for 4-6 hours to obtain a citric acid modified silicon dot (Si QDs-cit) solution; the mass ratio of the citric acid, EDC and NHS is 8:6-10:7-9.

[0024] Preferably, in step (5), citric acid, EDC and NHS are dissolved in ultrapure water, and then the Si QDs solution is added and reacted at room temperature for 6 hours, wherein the mass ratio of citric acid, EDC and NHS is 8:7:7.

[0025] In step (6), the citric acid modified silicon dot solution and the EDC solution (0.1-0.2 g / mL) are mixed and reacted for 5-15 minutes, and then NHS (0.05-0.08 g / mL) is added, and the reaction is carried out for 15-25 minutes, and then the amino-modified silica-coated gold nanoparticle solution is added, and the reaction is carried out at room temperature for 3-5 hours to obtain a silicon dot modified gold nanoparticle (AuNPs@SiO2@Si QDs) solution on the surface of silica; the volume ratio of the citric acid modified silicon dot solution, EDC, NHS and the amino-modified silica-coated gold nanoparticle solution is 10:1-2:1-2:5-15.

[0026] Preferably, in step (6), the Si QDs-cit solution and the EDC solution (0.113 g / mL) are mixed and reacted for 10 minutes, NHS (0.068 g / mL) is added, the reaction is carried out for 20 minutes, and then the Au NPs@SiO2-NH2 solution is added and the reaction is carried out at room temperature for 4 hours. The volume ratio of the SiQDs-cit solution, EDC, NHS and Au NPs@SiO2-NH2 solution is 10:1:1:10.

[0027] In step (7), the gold nanoparticle solution modified on the surface of silica by silicon dots and EDC solution (0.05-0.09 g / mL) are mixed and reacted for 5-15 minutes, and then NHS solution (0.03-0.05 g / mL) is added and reacted for 15-25 minutes, and then 3-aminophenylboronic acid (3-APBA) is added and reacted for 3-5 hours to obtain a plasma enhanced fluorescence fluorescent probe (P-probe); the volume ratio of the gold nanoparticle solution modified on the surface of silica by silicon dots, EDC, NHS and 3-aminophenylboronic acid is 10:1-3:1-2:1-10.

[0028] Preferably, in step (7), the Au NPs@SiO2@Si QDs solution and EDC (0.068 g / mL) are mixed and reacted for 10 min, then NHS (0.034 g / mL) is added and reacted for 20 min, and then 3-aminophenylboronic acid is added and reacted for 4 h to obtain a fluorescent probe (P-probe) of plasma enhanced fluorescence. The volume ratio of the Au NPs@SiO2@Si QDs solution, EDC, NHS and 3-aminophenylboronic acid is 10:1:1:10.

[0029] In the preparation of the present invention, the thickness of the silicon layer is controlled by step (2), the subsequent grafting is prepared by step (5), the fluorescence is enhanced by step (6), and the sensitivity is improved; and the grafted recognition substance is connected by step (7) to specifically detect ellagic acid.

[0030] The plasma enhanced fluorescence fluorescent probe prepared by the preparation method of the present invention.

[0031] Application of the fluorescent probe prepared by the preparation method of the present invention in detecting ellagic acid.

[0032] Application of the fluorescent probe prepared by the preparation method of the present invention in detecting ellagic acid in food.

[0033] Preferably, the fluorescent probe prepared by the preparation method is used in detecting ellagic acid in fruits.

[0034] A fluorescent probe based on gold nanoparticle structure-enhanced silicon dot fluorescence prepared by the present invention can be used to detect ellagic acid, and realize ellagic acid specific, rapid, and highly sensitive fluorescence detection. Quantum dots usually have a very high quantum yield in solution, so they are widely used in analytical determination, biological imaging and other fields, but in practical applications, they are not only easily quenched during assembly, but also the quantum yield is reduced, and this phenomenon is caused by the energy transfer of excitons from quantum dots to substrates or surface defect sites. Therefore, in order to overcome this defect, surface enhanced fluorescence (SEF), also known as metal enhanced fluorescence (MEF), can be used. The present invention uses silicon dioxide coated gold nanoparticles as plasma enhanced fluorescent nanoparticles, blue-emitting silicon quantum dots as plasma enhanced fluorescent substances, and 3-aminophenylboronic acid is modified on its surface, so that silicon dioxide coated gold nanoparticles are used as cores, and the structure of quantum dots grafted on the surface can prevent self-quenching due to agglomeration during quantum dot assembly, and also because the core is a metal gold nanoparticle that produces a metal enhanced fluorescence phenomenon, thereby solving the problem of quantum yield reduction. Realize ellagic acid specific, highly sensitive, and rapid fluorescence quantitative detection. The results show that the linear range of this fluorescent probe for detecting ellagic acid is 0.5-100 μM, and the detection time is about 5 minutes. Through the analysis of ellagic acid structural analogs such as salicylic acid, ethylene glycol, malic acid, citric acid and other types of interference substances, as well as the determination of interference analytes such as glucose and lactose that may exist in fruits, these substances do not interfere with the detection of ellagic acid and have high specificity. This fluorescent probe does not require complex synthesis steps or harsh synthesis conditions, and the fluorescence is stable and conducive to long-term storage, and the detection time is short (5 minutes). At the same time, the raw materials for the preparation of the fluorescent probe of the present invention are easy to obtain, the process is simple, the cost is low, and it is easy to mass produce.

[0035] The present invention studies the mechanism of ellagic acid quenching probe fluorescence. The results show that the ultraviolet absorption spectrum of ellagic acid does not overlap with the fluorescence emission spectrum of the fluorescent probe, so fluorescence resonance energy transfer is excluded to cause fluorescence quenching. Since the ultraviolet absorption peaks of ellagic acid and the fluorescent probe overlap, the quenching mechanism may be electron transfer. When the fluorescent probe is irradiated with light higher than the energy gap of the probe, the electrons in the probe may transition from the valence band to the conduction band. The electrons in the excited state may be absorbed or hinder the recombination of electron-hole pairs. If there is a strong electron absorption group, the charge in the probe conduction band can occupy the lowest unoccupied molecular orbital of ellagic acid.

[0036] At present, many fluorescent probes cannot be applied to ellagic acid, mainly due to the lack of recognition elements, and ellagic acid has no suitable aptamer. The focus of the present invention is to use plasma enhanced fluorescence to achieve fluorescence enhancement of silicon dots, improve the sensitivity of detection, and use aminophenylboronic acid to identify ellagic acid, thereby improving the specificity of detection. The present invention studies and finds the influence of 3-aminophenylboronic acid on the detection effect of fluorescent probes. The fluorescent probes that are not grafted and grafted with 3-aminophenylboronic acid are incubated with 50μM ellagic acid solution, and the fluorescence changes are observed. The results show that when there is 3-aminophenylboronic acid, the fluorescence quenching effect is more significant, indicating that when there is phenylboronic acid, the fluorescent probe has a better detection effect.

[0037] The present invention applies plasma enhanced fluorescence technology to ellagic acid detection for the first time, and has a lower detection limit than the liquid phase detection method used in the prior art. Due to plasma enhanced fluorescence, the sensitivity of this probe is significantly higher than that of general detection technology, and the linear range is significantly wider than that of general detection technology.

[0038] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0039] The invention prepares a fluorescent probe of plasma enhanced fluorescence, which is not only simple and convenient to prepare, but also has good stability, strong specificity and high sensitivity. The probe can be used for quantitative detection of ellagic acid (EA) in foods such as fruits, and is more efficient, cost-saving and accurate.

[0040] The plasma enhanced fluorescence fluorescent probe prepared by the invention improves the sensitivity of the fluorescent probe in detecting ellagic acid, and the linear range is significantly wider than that of general detection technology.

[0041] The present invention enhances the fluorescence of silicon dots based on the structure of gold nanoparticles to improve the detection sensitivity, improve the luminescence intensity of silicon dots, have an "on-off" characteristic dependent on ellagic acid concentration, and can be used as a specific ellagic acid concentration indicator. The probe prepared by the present invention can effectively solve the shortcomings of the existing ellagic acid detection, such as complicated operation, expensive instruments, or large environmental interference. The present invention not only detects ellagic acid simply and quickly, but also can detect different substances in food by changing the recognition element. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Ultraviolet spectra of AuNPs (curve a) and AuNPs@SiO2 (curve b) prepared in the present invention.

[0043] Figure 2 This is the fluorescence emission spectrum of Si QDs prepared in the present invention.

[0044] Figure 3 It is the ultraviolet absorption peak of Au NPs (curve b) prepared in the present invention and the fluorescence emission peak of Si QDs (curve a).

[0045] Figure 4 Transmission electron microscopy images of AuNPs (a) and AuNPs@SiO2 (b) prepared in the present invention.

[0046] Figure 5 Fluorescence emission spectra of Au NPs@SiO2@Si QDs (curve a) solution and Si QDs-cit (curve b) prepared in the present invention.

[0047] Figure 6 The present invention provides a fluorescence emission spectrum diagram of the fluorescent probe prepared in response to ellagic acid of different concentrations.

[0048] Figure 7 The linear relationship diagram of the fluorescent probe prepared by the present invention and the response to different concentrations of ellagic acid is shown.

[0049] Figure 8 The ultraviolet spectra of the fluorescent probe (curve a) and EA (curve b) prepared in the present invention and the fluorescence emission of the fluorescent probe (curve c) are shown.

[0050] Fig. 9 The diagram is a detection effect diagram of the fluorescent probes without grafting and grafting 3-aminophenylboronic acid prepared by the present invention.

[0051] Fig.10 The changes in fluorescence intensity of Si QDs-cit (curve a), Au NPs@SiO2@Si QDs (curve b) and fluorescent probe (curve c) prepared in the present invention vary with time.

[0052] Fig.11The fluorescence intensities of Si QDs-cit (curve a), Au NPs@SiO2@Si QDs (curve b) and fluorescent probe (curve c) prepared in the present invention at different temperatures.

[0053] Fig.12 The graph is a fluorescence change diagram of the fluorescent probe prepared in the present invention when incubated with ellagic acid for different time periods.

[0054] Fig.13 This is a fluorescence change diagram of the reaction between the fluorescent probe prepared in the present invention and the interfering substance of ellagic acid.

[0055] Fig.14 This is an electric field simulation diagram of the gold nanoparticles prepared in the present invention.

[0056] Fig.15 Infrared spectra of Au NPs (curve a), Au NPs@SiO2 (curve b), Si QDs (curve c), SiQDs-cit (curve d) and Au NPs@SiO2@Si QDs (curve e) prepared in the present invention.

[0057] Fig.16 The zeta potential diagrams of Au NPs, Au NPs@SiO2, Si QDs, Si QDs-cit and Au NPs@SiO2@SiQDs and fluorescent probes prepared in the present invention.

[0058] Fig.17 Fluorescence lifetime diagrams of transient fluorescence detection of Si QDs-cit solution (diluted 10 times) (a) and Au NPs@SiO2@Si QDs solution (b) prepared in the present invention.

[0059] Fig.18 This is an X-ray photoelectron spectrum of the fluorescent probe prepared by the present invention.

[0060] Fig.19 The fluorescence spectra of the fluorescent probe prepared in the present invention (curve a) and the fluorescent probe mixed with the actual sample extract (curve b) are shown.

[0061] Fig. 20 The figure is a linear relationship diagram between the concentration of ellagic acid and the peak area prepared in the present invention.

[0062] Fig.21 The high performance liquid chromatogram of the sample extract prepared in the present invention. DETAILED DESCRIPTION

[0063] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0064] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0065] Among them, ellagic acid solid was purchased from Shanghai Yuanye Biotechnology Co., Ltd., and other commercially available ones are all available.

[0066] Example 1

[0067] 1. Preparation of gold nanoparticle solution

[0068] 50 mL of chloroauric acid aqueous solution (mass fraction 0.01%) was heated to boiling, and 0.5 mL of sodium citrate solution (mass fraction 1%) was added. After 70 seconds, the solution changed from colorless to wine red, and continued to boil for 5 minutes, then the heating was turned off to obtain a gold nanoparticle (Au NPs) solution.

[0069] 2. Preparation of Silica-coated Gold Nanoparticle Solution

[0070] 20 mL of anhydrous ethanol was added to a round-bottom flask, followed by 10 mL of Au NPs solution, 0.7 mL of ammonia water, and then 1.1 mL of TEOS ethanol solution (10 mM) and reacted at room temperature for 12 h to obtain a solution of gold nanoparticles encapsulated with silica (Au NPs@SiO2).

[0071] 3. Preparation of amino-functionalized silica-coated gold nanoparticle solution

[0072] 1.5 mL of APTMS solution (1 mM) was added to 15 mL of Au NPs@SiO2 solution and reacted at 37°C for 5 h, and then at 50°C for 1 h. The volume of the solution was fixed by rotary evaporation to 5 mL to obtain amino-functionalized silica-coated gold nanoparticles (Au NPs@SiO2-NH2) solution.

[0073] 4. Preparation of silicon dots

[0074] Add 0.318 g of sodium citrate into a round-bottom flask, then add 8 mL of glycerol, pass argon, stir and react for 20 min, then add 2 mL of APTES and react for 10 min. Move into an oil bath at 185 °C and react for 1.5 h. During the reaction, continue to pass argon to obtain a silicon dot (Si QDs) solution.

[0075] 5. Preparation of citric acid modified silicon dot solution

[0076] Add 0.008 g of citric acid to a round-bottom flask, add 19 mL of ultrapure water, then add 0.007 g of EDC, 0.007 g of NHS and 1 mL of Si QDs solution (take 0.1 mL of Si QDs in step 4 and dilute it to 1 mL with water), react at room temperature for 6 h to obtain a citric acid-modified silicon dot (Si QDs-cit) solution.

[0077] 6. Preparation of gold nanoparticle solution modified with silicon dots on the surface of silica

[0078] 1 mL of Si QDs-cit solution was added to a round-bottom flask, and 0.1 mL of EDC solution (0.113 g / mL) was added, and the mixture was reacted at room temperature for 10 min. Then 0.1 mL of NHS solution (0.068 g / mL) was added, and the mixture was reacted at room temperature for 20 min. Then 1 mL of Au NPs@SiO2-NH2 solution was added, and the mixture was reacted at room temperature for 4 h to obtain a solution of gold nanoparticles (Au NPs@SiO2@SiQDs) modified on the surface of silica.

[0079] 7. Preparation of fluorescent probes

[0080] 1 mL of Au NPs@SiO2@Si QDs solution was added to a round-bottom flask, and 0.1 mL of EDC solution (0.057 g / mL) was added, mixed and reacted at room temperature for 10 min, and then 0.1 mL of NHS solution (0.034 g / mL) was added, and reacted at room temperature for 20 min. Then 1 mL of 3-aminophenylboronic acid solution (0.0004 g / mL) was added and reacted at room temperature for 4 h to obtain a plasmon-enhanced fluorescence fluorescent probe (Au NPs@SiO2@Si QDs-3-APBA).

[0081] Example 2

[0082] UV-visible spectra of Au NPs solution and Au NPs@SiO2 solution prepared in Example 1

[0083] 2 mL of the Au NPs solution and Au NPs@SiO2 solution prepared in Example 1 were taken for UV detection.

[0084] UV-Visible spectrum test: Test the UV-Visible spectrum of the above solution. The UV-Visible spectrum uses pure water as the reference solution and scans the spectrum in the wavelength range of 300nm-700nm. The obtained UV-Visible spectrum (see Figure 1 ), Figure 1 Curve a in the middle shows that the maximum absorbance of the Au NPs solution is around 529 nm, and is stronger than that of the Au NPs@SiO2 solution at the same concentration ( Figure 1Curve b) indicates that Au NPs solution and Au NPs@SiO2 solution were successfully synthesized.

[0085] Example 3

[0086] Fluorescence emission spectrum of Si QDs prepared in Example 1

[0087] 0.1 mL of the Si QDs stock solution prepared in Example 1 was diluted 200 times, and then fluorescence detection was performed.

[0088] Fluorescence spectrum test: Take the above solution to measure the fluorescence emission spectrum. The fluorescence emission spectrum was determined with 380nm excitation, 5nm / 5nm slit width for excitation and emission, and 700V voltage. The obtained fluorescence emission spectrum (see Figure 2 ), Figure 2 It was shown that SiQDs had a fluorescence emission peak at 450nm, indicating the successful synthesis of Si QDs.

[0089] Example 4

[0090] Example 1 Overlapping graph of the ultraviolet absorption peak of Au NPs and the fluorescence emission peak of Si QDs

[0091] 2 mL of Au NPs solution was taken for UV detection, and 1 mL of silicon dot dilution solution (0.1 mL of Si QDs in step 4 of Example 1 was diluted to 1 mL with water) was taken for fluorescence detection.

[0092] The UV-visible spectrum uses pure water as the reference solution and scans the spectrum in the wavelength range of 300nm-700nm. Fluorescence spectrum test: Take the above solutions and measure the fluorescence emission spectra respectively. The fluorescence emission spectrum is determined by excitation at 380nm, the slit width of excitation and emission is 5nm / 5nm, and the voltage is 700V. UV-visible spectrum test: Test the UV-visible spectrum of the above solution. The fluorescence emission peak of Si QDs ( Figure 3 Curve a) and the UV absorption peak of Au NPs ( Figure 3 Curve b) is combined and compared to obtain the spectrum overlap diagram (see Figure 3 ), Figure 3 It shows that the UV absorption peak and the fluorescence emission peak partially overlap, indicating that Au NPs can theoretically enhance the fluorescence intensity of Si QDs.

[0093] Example 5

[0094] Example 1 Transmission electron microscopy images of Au NPs and Au NPs@SiO2

[0095] Two copper meshes were picked up with tweezers, and were soaked in Au NPs solution and Au NPs@SiO2 solution respectively. Then, they were taken out and placed in a disposable culture dish lined with filter paper. After the copper meshes were dried, they were placed in the sample injector of the transmission electron microscope. The transmission electron microscope images (see Figure 4 ). Figure 4 Middle a shows that the Au NPs are spherical in shape, with a particle size of approximately 41 nm; Figure 4 Figure b shows that there is silicon dioxide on the surface of Au NPs, and the thickness is about 4.92nm, indicating that Au NPs@SiO2 was successfully synthesized.

[0096] Example 6

[0097] Fluorescence emission spectrum of Au NPs@SiO2@Si QDs solution prepared in Example 1.

[0098] The Au NPs@SiO2@Si QDs solution was synthesized according to the method of step (6) of Example 1; at the same time, the Au NPs@SiO2-NH2 solution was replaced with ultrapure water according to the method of step (6) of Example 1 to obtain a Si QDs-cit solution of the same dilution concentration.

[0099] Fluorescence spectrum test: Take the above solutions and measure the fluorescence emission spectrum. The fluorescence emission spectrum was determined with 380nm excitation, 5nm / 5nm slit width for excitation and emission, and 700V voltage. The obtained fluorescence emission spectrum (see Figure 5 ), Figure 5 Show Au NPs@SiO2@Si QDs solution ( Figure 5 The fluorescence intensity of curve a) is higher than that of Si QDs-cit solution with the same dilution concentration ( Figure 5 Curve b), the fluorescence intensity of Au NPs@SiO2@Si QDs solution is about 8.4 times that of Si QDs-cit solution. The experimental results show that Au NPs solution can enhance the fluorescence of Si QDs.

[0100] Example 7

[0101] Fluorescence emission spectra of the fluorescent probe prepared in Example 1 in response to different concentrations of ellagic acid.

[0102] Weigh 0.302 mg of ellagic acid and add 1 mL of pure water to prepare a mother solution with a concentration of 1 mmol / L. Use the mother solution to prepare ellagic acid methanol solutions with concentrations of 0.1 μM, 0.5 μM, 1 μM, 5 μM, 10 μM, 20 μM, 50 μM, 100 μM, 200 μM and 500 μM, respectively. Take the fluorescent probe prepared in Example 1 and ellagic acid of different concentrations in a volume ratio of 1:1, incubate at room temperature for 2 h, and test the fluorescence emission spectrum.

[0103] Fluorescence spectrum test: Take the mixed solution after incubation and measure the fluorescence emission spectrum. The fluorescence emission spectrum was determined with 380nm excitation, 5nm / 5nm slit width for excitation and emission, and 700V voltage. The obtained fluorescence emission spectrum (see Figure 6 ), Figure 6 It shows that the fluorescence intensity of the fluorescent probe gradually decreases with the increase of ellagic acid concentration. When the ellagic acid concentration is 0.5-100 μM, it is linearly correlated with the fluorescence intensity of the fluorescent probe, and the fitting linearity is shown in Figure 2. Figure 7 ), Figure 7 The fitting curve is shown as y = 0.0064x + 0.0051 (R 2 =0.9954), and the detection limit was 0.14 μM. This indicates that the fluorescent probe prepared by the present invention has the ability to detect ellagic acid in a fluorescence "off" mode.

[0104] Example 8

[0105] Ultraviolet spectra of the fluorescent probe and EA prepared in Example 1 and the fluorescence emission diagram of the fluorescent probe.

[0106] Fluorescence spectrum test: Fluorescence emission spectrum was determined with 380nm excitation, 5nm / 5nm slit width for excitation and emission, and 700V voltage. The UV-visible spectrum was scanned in the wavelength range of 200nm-700nm with pure water as reference liquid (see Figure 8 ).like Figure 8 As shown, the results showed that ellagic acid ( Figure 8 Curve a) and fluorescent probe ( Figure 8 The ultraviolet absorption peak of curve b) overlaps with the emission spectrum of the fluorescent probe ( Figure 8 Curve c) does not overlap, so the quenching mechanism of the fluorescence of the ellagic acid probe in the present invention may be photoelectron transfer.

[0107] Example 9

[0108] Detection effect diagram of the fluorescent probes grafted with and not grafted with 3-aminophenylboronic acid prepared in Example 1.

[0109] The 1 mL 3-aminophenylboronic acid solution added in step 7 of Example 1 was replaced with 1 mL ultrapure water to prepare a fluorescent probe without 3-aminophenylboronic acid grafted therewith. The grafted and ungrafted fluorescent probes were incubated with 0.5 mL and 0.5 mL of 50 μM ellagic acid solution, respectively, for 2 h to observe the fluorescence changes of the two.

[0110] Fluorescence spectrum test: Take the mixed solution after incubation and measure the fluorescence emission spectrum. The fluorescence emission spectrum was determined with 380nm excitation, 5nm / 5nm slit width for excitation and emission, and 700V voltage. Fig. 9 .like Fig. 9 As shown, after grafting 3-aminophenylboronic acid, the fluorescence intensity decreased to a greater extent, indicating that the fluorescent probe grafted with 3-aminophenylboronic acid has a better detection effect.

[0111] Example 10

[0112] Detection graph of the fluorescence intensity stability of the fluorescent probe prepared in Example 1 at different times.

[0113] Take 7 1 mL portions of the fluorescent probe prepared in Example 1, Si QDs-cit solution (diluted 10 times), and AuNPs@SiO2@Si QDs solution, and perform fluorescence detection at 1d, 2d, 3d, 4d, 5d, 6d, and 7d to study the changes in the fluorescence intensity of these 7 samples.

[0114] Fluorescence spectrum test: Fluorescence emission spectrum was measured with 380nm excitation, 5nm / 5nm slit width for excitation and emission, and 700V voltage. The obtained fluorescence intensity change diagram (see Fig.10 ), Fig.10 It shows that with the extension of time, Si QDs-cit solution ( Fig.10 Curve a), Au NPs@SiO2@Si QDs solution ( Fig.10 Curve b) and fluorescent probe ( Fig.10 The fluorescence intensity of curve c) does not change significantly, indicating that the fluorescence stability of the fluorescent probe prepared by the present invention is conducive to long-term storage.

[0115] Embodiment 11

[0116] Detection diagram of the fluorescence intensity stability of the fluorescent probe prepared in Example 1 at different temperatures.

[0117] Take 7 portions of 1 mL of the fluorescent probe prepared in Example 1, Si QDs-cit solution (diluted 10 times), and AuNPs@SiO2@Si QDs solution, and place them in a water bath at 4°C, 20°C, 25°C, 30°C, 37°C, 45°C, 55°C, and 65°C for 1 hour. Test the fluorescence intensity of the 7 samples.

[0118] Fluorescence spectrum test: Fluorescence emission spectrum was measured with 380nm excitation, 5nm / 5nm slit width for excitation and emission, and 700V voltage. The obtained fluorescence intensity change diagram (see Fig.11 ), Fig.11 It shows that with the change of temperature, Si QDs-cit solution ( Fig.11 Curve a), Au NPs@SiO2@Si QDs solution ( Fig.11 Curve b) and fluorescent probe ( Fig.11The fluorescence intensity of curve c) does not change significantly, indicating that the fluorescent probe prepared by the present invention is stable at different temperatures.

[0119] Example 12

[0120] Fluorescence change diagram of the fluorescent probe prepared in Example 1 after incubation with ellagic acid for different time periods

[0121] Thirteen portions of 0.5 mL of the fluorescent probe prepared in Example 1 were mixed with 0.5 mL of a 50 μM ellagic acid solution, and the mixing time at room temperature was 0 min, 1 min, 2 min, 3 min, 4 min, 5 min, 10 min, 15 min, 20 min, 30 min, 60 min, 90 min and 120 min, respectively. After mixing, the samples were subjected to fluorescence detection to study the change in fluorescence intensity.

[0122] Fluorescence spectrum test: Fluorescence emission spectrum was measured with 380nm excitation, 5nm / 5nm slit width for excitation and emission, and 700V voltage. The obtained fluorescence intensity change diagram (see Fig.12 ), Fig.12 It shows that the fluorescence intensity gradually decreases with the extension of time, and reaches equilibrium at about 5 minutes, indicating that the fluorescent probe can react quickly with ellagic acid.

[0123] Embodiment 13

[0124] Fluorescence change diagram of the reaction between the fluorescent probe prepared in Example 1 and the interfering substance of ellagic acid

[0125] 0.5 mL of different interfering substance solutions were added to the above 0.5 mL fluorescent probe solution, and the fluorescence emission spectra were measured in time after shaking at 25 ° C for 2 hours. Among them, the concentration of ellagic acid was 45 μM, and the final concentrations of salicylic acid, ethylene glycol, malic acid, citric acid, glucose, lactose, calcium chloride (CaCl2), magnesium chloride (MgCl2) and sodium chloride (NaCl) were all 450 μM. Then, the above 900 μM interfering substance and 90 μM ellagic acid were mixed in equal volumes, and then the fluorescent probe and the above solution were mixed in equal volumes to detect the changes in their fluorescence emission intensity.

[0126] Fluorescence emission spectrum was determined with 380nm excitation: the slit widths of excitation and emission were 5nm / 5nm, and the measurement voltage was 700V. The fluorescence spectrum obtained based on the fluorescence intensity of the fluorescent probe at 450nm and the fluorescence response of other interfering substances (see Fig.13 ). Fig.13 The results show that the fluorescent probe will produce strong fluorescence quenching only when the solution contains ellagic acid, indicating that the fluorescent probe prepared by the present invention is specific to ellagic acid.

[0127] Embodiment 14

[0128] Electric field simulation diagram of the gold nanoparticles prepared in Example 1

[0129] The FDTD software was used to simulate the electric field strength around the gold nanoparticles prepared in Example 1 (see Fig.14 ), Fig.14 The maximum field strength around gold nanoparticles is 3.7 (V / m) 2 . This indicates that gold nanoparticles can enhance the fluorescence of silicon dots through the surrounding electric field.

[0130] Embodiment 15

[0131] Infrared spectra of freeze-dried powders of Au NPs solution, Au NPs@SiO2 solution, Si QDs solution, Si QDs-cit solution and Au NPs@SiO2@Si QDs solution prepared in Example 1

[0132] The material prepared in Example 1 was tested using a Fourier transform infrared spectrometer (FTIR), and the infrared spectrum obtained was Fig.15 , Fig.15 Display 1095cm -1 It is the antisymmetric stretching vibration peak of Si-O-Si, at 1724cm -1 (C=O) and 3449cm -1 (OH) near the absorption band (see Fig.15 Curve a), which confirms the presence of carboxyl groups on the surface of gold nanoparticles; 789 cm -1 and 466cm -1 is the symmetrical stretching vibration peak of Si-O bond (see Fig.15 Curve b); 1637cm -1 is the stretching vibration peak of NH, 850cm -1 is the NH out-of-plane deformation vibration peak (see Fig.15 Curve c); 1716cm -1 It is the stretching vibration peak of the C=O double bond on the carboxyl group, 3350cm -1 is the NH stretching vibration peak, 1660cm -1 is the stretching vibration peak of C=O on the amide group, indicating that citric acid is modified on the surface of the silicon dots through amidation reaction (see Fig.15 Curve d); 1640cm -1 It is the stretching vibration peak of C=O on the amide group, 3270cm -1is the NH stretching vibration peak, 1075cm -1 is the antisymmetric stretching vibration peak of Si-O-Si, indicating the successful synthesis of Au NPs@SiO2@Si QDs (see Fig.15 Curve e).

[0133] Example 16

[0134] The Au NPs solution, Au NPs@SiO2 solution, Si QDs solution, Si QDs-cit solution and Au NPs@SiO2@Si QDs solution prepared in Example 1 were used to detect the zeta potential of the fluorescent probe.

[0135] The materials prepared in Example 1 were tested using a zeta potential and particle size analyzer to obtain a potential bar graph of each material (see Fig.16 ), Fig.16 It shows that the negative potential of Au NPs is stronger than that of Au NPs@SiO2, indicating that silica is wrapped around gold nanoparticles; the potentials of Si QDs and Si QDs-cit also change, indicating that Si QDs-cit is successfully synthesized; the potential of AuNPs@SiO2@Si QDs is stronger than that of Si QDs-cit, indicating the successful synthesis of Au NPs@SiO2@Si QDs; the potential of the fluorescent probe is weaker than that of Au NPs@SiO2@Si QDs, indicating the successful synthesis of the fluorescent probe.

[0136] Embodiment 17

[0137] Fluorescence lifetime diagram of transient fluorescence detection of Si QDs-cit solution and Au NPs@SiO2@Si QDs solution prepared in Example 1

[0138] The above samples were detected using a transient fluorescence spectrometer to obtain fluorescence lifetime diagrams (see Fig.17 ), Fig.17 It is shown that the Si QDs-cit( Fig.17 The fluorescence lifetime of curve a) is 3.50ns, and Au NPs@SiO2@Si QDs ( Fig.17 The fluorescence lifetime of curve b) is 3.05ns. The fluorescence lifetime of Au NPs@SiO2@Si QDs is shorter than that of Si QDs-cit, indicating that Si QDs are successfully modified onto the surface of Au NPs@SiO2, achieving the effect of fluorescence enhancement.

[0139] Embodiment 18

[0140] The fluorescent probe prepared in Example 1 was subjected to X-ray photoelectron spectroscopy analysis.

[0141] The fluorescent probe solution was dialyzed with 1KD dialysis tape for 2 days and freeze-dried in a freeze dryer for 24 hours to obtain a fluorescent probe solid.

[0142] The fluorescent probe solid was analyzed using an X-ray photoelectron spectrometer to obtain an X-ray photoelectron spectrum (see Fig.18 ). Fig.18 The results show that the B1s peak is at 191.1eV, the Si 2p peak is at 102.1eV, and the C 1s, N 1s, and O1s peaks are at 284.8eV, 399.57eV, and 531.9eV, respectively. The above results show that 3-aminophenylboronic acid is successfully modified on the surface of Au NPs@SiO2@SiQDs, indicating the successful synthesis of the fluorescent probe.

[0143] Embodiment 19

[0144] Fluorescence change diagram after mixing the fluorescent probe prepared in Example 1 with the actual sample extract

[0145] Weigh 0.2g of pomegranate peel powder, add 4mL of anhydrous methanol, and ultrasonicate for 1h. Take 2mL of supernatant and pass it through a solid phase extraction column (Venusil MP C18, 4.6×250mm, 5μm, manufacturer: Tianjin Bona Aiger Technology Co., Ltd.), then elute the ellagic acid in the column with 50% methanol solution to obtain the actual sample extract. Dilute the extract 10 times, take 0.5mL of the extract and 0.5mL of the fluorescent probe, mix and react for 2h, and detect the change in its fluorescence intensity.

[0146] Fluorescence emission spectrum was determined with 380nm excitation: the slit widths for excitation and emission were 5nm / 5nm, and the measurement voltage was 700V. The fluorescence spectrum obtained based on the fluorescence intensity of the fluorescent probe at 450nm and the response of the sample extract (see Fig.19 ). Fig.19 Display fluorescent probes ( Fig.19 Curve a) and the fluorescent probe after mixing with the sample ( Fig.19 Curve b) shows a fluorescence spectrum. The fluorescence intensity of the two mixed products is slightly lower than that of the mixed products. Figure 7 Based on the obtained linear relationship, the EA concentration in the sample was calculated to be 210.8 μM.

[0147] Embodiment 20

[0148] The extract obtained in Example 17 was detected by high performance liquid chromatography

[0149] Different concentrations of ellagic acid (0.01 mg / mL, 0.02 mg / mL, 0.03 mg / mL, 0.04 mg / mL, 0.06 mg / mL and 0.08 mg / mL) were prepared, filtered with a 0.22 μm organic filter head, and ellagic acid solutions of different concentrations were detected with a high performance liquid chromatograph to obtain the relationship between the concentration and the peak area of ​​ellagic acid, and to fit the linearity. The concentration of ellagic acid in the sample was calculated by the fitted linearity and the peak area of ​​ellagic acid in the extract.

[0150] Ellagic acid was detected using a UV detector of Shimadzu's HPLC. Mobile phase A was 0.1% formic acid solution and mobile phase B was acetonitrile. Under gradient elution, the proportion of acetonitrile changed as follows: first, from 10% to 45% at 0-30min; then, from 45% to 100% at 31-33min; and finally, from 100% to 10% at 34-35min. The detection time of a single sample was 35min, and the retention time was around 17.5min. The linear fitting was y=262.65058x–3.04574, R 2 =0.9901. The results of HPLC detection of sample extracts are shown in Fig.21 ,Will Fig.21 The peak area obtained is Fig. 20 The linear combination of the results showed that the concentration of ellagic acid detected by HPLC was 211.4 μM. This result was compared with the result of Example 19, indicating that the result of detecting ellagic acid by the fluorescent probe was credible.

[0151] Embodiment 21

[0152] The fluorescent probe prepared in Example 1 was subjected to a spike recovery experiment.

[0153] Weigh 3 portions of 0.2 g of pomegranate peel powder, add 1 mL of 200 μM, 400 μM and 600 μM EA solution, add 3 mL of anhydrous methanol (EA is 50 μM, 100 μM and 150 μM after dilution), and then prepare the spiked extract according to the extraction steps of Example 19. The 10-fold diluted extract was mixed with an equal volume of the fluorescent probe for 2 h, and the change in its fluorescence intensity was detected.

[0154] The fluorescence emission spectrum was determined with 380 nm excitation: the slit widths of excitation and emission were 5 nm / 5 nm, and the measurement voltage was 700 V. According to the change in fluorescence intensity of the fluorescent probe at 450 nm, the spiked recovery results were calculated (as shown in Table 1). Table 1 shows that the spiked recovery rate of the fluorescent probe is between 100.16 and 107.81%, indicating that this probe can be accurately used for the quantitative detection of ellagic acid.

[0155] Table 1 Spiked recovery results

[0156]

[0157] At the same time, in combination with the method of Example 7 and the method of Example 20, the detection limit and detection range of the fluorescent probe prepared in Example 1 of the present invention for pomegranate peel were determined. At present, the common detection method for ellagic acid is liquid chromatography, and there are few fluorescence detection methods. There is no plasma enhanced fluorescence applied to detect ellagic acid, and the detection results are shown in Table 2 below. Although the electrochemical detection method may have a lower detection limit, its electrode life is short, and different electrodes will result in different detection results. Therefore, after comparison, it is shown that the fluorescence detection method of the present invention is better.

[0158] Table 2 Comparison of common EA detection methods and the method of the present invention

[0159]

[0160] Embodiment 22

[0161] Example 22 is the same as Example 1, except that: in step (1), the mass ratio of chloroauric acid to sodium citrate is 1:5. In step (2), anhydrous ethanol and ammonia water are added to the gold nanoparticle solution, and then TEOS solution is added to continue the reaction for 6 hours to obtain a silica-wrapped gold nanoparticle solution; the volume ratio of the gold nanoparticle solution, anhydrous ethanol, ammonia water and TEOS is 100:150:3:7. In step (3), APTMS is reacted with the silica-wrapped gold nanoparticle solution at 30°C for 7 hours, and then at 40°C for 2 hours to obtain an amino-modified silica-wrapped gold nanoparticle solution; the volume ratio of APTMS to the silica-wrapped gold nanoparticle solution is 1:10. In step (4), 0.2g of sodium citrate and 8mL of glycerol are reacted at room temperature for 20 minutes, and then APTES is added to continue the reaction for 5 minutes, and then at 170°C for 2 hours to obtain a silicon dot solution; the volume ratio of glycerol to APTES is 8:1. In step (5), citric acid, EDC and NHS are dissolved in ultrapure water, and then 1 mL of the diluted silicon dot solution is added, and the mixture is reacted at room temperature for 6 hours to obtain a citric acid-modified silicon dot solution; the mass ratio of the citric acid, EDC and NHS is 8:6:7. In step (6), the citric acid-modified silicon dot solution and 0.1 g / mL EDC solution are mixed and reacted for 5 minutes, and then 0.05 g / mL NHS solution is added, and the mixture is reacted for 15 minutes, and then an amino-modified silica-coated gold nanoparticle solution is added, and the mixture is reacted at room temperature for 3 hours to obtain a gold nanoparticle solution with silicon dots modified on the surface of silica; the volume ratio of the diluted citric acid-modified silicon dot solution, EDC, NHS and amino-modified silica-coated gold nanoparticle solution is 10:1:1:5. In step (7), the gold nanoparticle solution modified on the surface of silicon dioxide with silicon dots and 0.05 g / mL EDC solution are mixed and reacted for 5 minutes, and then 0.03 g / mL NHS solution is added and reacted for 15 minutes, and then 3-aminophenylboronic acid is added and reacted for 3 hours to obtain a fluorescent probe of plasma enhanced fluorescence; the volume ratio of the gold nanoparticle solution modified on the surface of silicon dioxide with silicon dots, EDC, NHS and 3-aminophenylboronic acid is 10:1:1:10.

[0162] Embodiment 23

[0163] The method of Example 23 is the same as that of Example 1, except that: in step (1), the mass ratio of chloroauric acid to sodium citrate is 1:10. In step (2), anhydrous ethanol and ammonia water are added to the gold nanoparticle solution, and then TEOS solution is added to continue the reaction for 24 hours to obtain a silica-encapsulated gold nanoparticle solution; the volume ratio of the gold nanoparticle solution, anhydrous ethanol, ammonia water and TEOS is 100:800:10:15. In step (3), APTMS is reacted with the silica-encapsulated gold nanoparticle solution at 40°C for 3 hours, and then at 60°C for 1 hour to obtain an amino-modified silica-encapsulated gold nanoparticle solution; the volume ratio of APTMS to the silica-encapsulated gold nanoparticle solution is 2:10. In step (4), 0.4 g of sodium citrate and 8 mL of glycerol are reacted at room temperature for 40 minutes, and then APTES is added to continue the reaction for 15 minutes, and then at 190°C for 1 hour to obtain a silicon dot solution; the volume ratio of glycerol to APTES is 8:2. In step (5), citric acid, EDC and NHS are dissolved in ultrapure water, and then 2 mL of the diluted silicon dot solution is added and reacted at room temperature for 4 hours to obtain a citric acid modified silicon dot solution; the mass ratio of the citric acid, EDC and NHS is 8:10:9. In step (6), the 10-fold diluted citric acid modified silicon dot solution and 0.2 g / mL EDC solution are mixed and reacted for 15 minutes, and then 0.08 g / mL NHS solution is added and reacted for 25 minutes, and then amino-modified silica-coated gold nanoparticle solution is added and reacted at room temperature for 5 hours to obtain a silicon dot modified on the surface of silica gold nanoparticle solution; the volume ratio of citric acid modified silicon dot solution, EDC, NHS and amino-modified silica-coated gold nanoparticle solution is 10:2:2:15. In step (7), the gold nanoparticle solution modified on the surface of silica by silicon dots and 0.09 g / mL EDC solution are mixed and reacted for 15 minutes, and then 0.05 g / mL NHS solution is added and reacted for 25 minutes, and then 3-aminophenylboronic acid is added and reacted for 5 hours to obtain a fluorescent probe of plasma enhanced fluorescence; the volume ratio of the gold nanoparticle solution modified on the surface of silica by silicon dots, EDC, NHS and 3-aminophenylboronic acid is 10:3:2:4.

Claims

1. A method for preparing a fluorescent probe for plasma enhanced fluorescence, characterized in that: The steps include: (1) adding sodium citrate to a chloroauric acid solution and heating the solution to produce a gold nanoparticle solution; (2) reacting anhydrous ethanol, tetraethyl orthosilicate (TEOS) and ammonia water in a gold nanoparticle solution to obtain a gold nanoparticle solution coated with silica; (3) reacting triaminopropyltrimethoxysilane (APTMS) with a solution of gold nanoparticles coated with silica to obtain a solution of gold nanoparticles coated with silica with surface modified amino groups; (4) reacting sodium citrate, triaminopropyltriethoxysilane (APTES) and glycerol to obtain a silicon dot solution; (5) reacting citric acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), N-hydroxysuccinimide (NHS) and the silicon dot solution to obtain a citric acid-modified silicon dot solution; (6) reacting a citric acid-modified silicon dot solution, EDC, NHS, and a silicon dioxide-coated gold nanoparticle solution with surface-modified amino groups to obtain a silicon dot-modified gold nanoparticle solution on the surface of silicon dioxide; (7) 3-Aminophenylboronic acid, EDC, NHS and a solution of gold nanoparticles modified with silicon dots on the surface of silica were reacted to obtain a plasmon-enhanced fluorescent probe.

2. The preparation method according to claim 1, characterized in that: In step (1), the chloroauric acid aqueous solution is heated to boiling, and the sodium citrate solution is added to react, and the solution is allowed to continue boiling for 3-7 minutes after turning into wine red, and then the heating is turned off to obtain a gold nanoparticle solution; the mass ratio of the chloroauric acid to the sodium citrate is 1:1-10.

3. The preparation method according to claim 1, characterized in that: In step (2), anhydrous ethanol and ammonia water are added to the gold nanoparticle solution, and then TEOS solution is added to continue the reaction for 6-24 hours to obtain a silica-coated gold nanoparticle solution; the volume ratio of the gold nanoparticle solution, anhydrous ethanol, ammonia water and TEOS is 100:150-800:3-10:7-15.

4. The preparation method according to claim 1, characterized in that: In step (3), APTMS and the silica-coated gold nanoparticle solution are reacted at 30-40° C. for 3-7 h, and then reacted at 40-60° C. for 1-2 h to obtain a silica-coated gold nanoparticle solution with surface modified amino groups; the volume ratio of the APTMS to the silica-coated gold nanoparticle solution is 1-2:

10.

5. The preparation method according to claim 1, characterized in that: In step (4), 0.2-0.4 g of sodium citrate and 8 mL of glycerol are reacted at room temperature for 20-40 min, and then 1-3 mL of APTES is added and the reaction is continued for 5-15 min, and then the reaction is carried out at 170-190° C. for 1-2 h to obtain a silicon dot solution; the volume ratio of glycerol to APTES is 8:1-2.

6. The preparation method according to claim 1, characterized in that: In step (5), citric acid, EDC and NHS are dissolved in ultrapure water, and then 1-2 mL of the diluted silicon dot solution is added and reacted at room temperature for 4-6 h to obtain a citric acid-modified silicon dot solution; the mass ratio of the citric acid, EDC and NHS is 8:6-10:7-9.

7. The preparation method according to claim 1, characterized in that: In step (6), the citric acid modified silicon dot solution and 0.1-0.2 g / mL EDC solution are mixed and reacted for 5-15 min, and then 0.05-0.08 g / mL NHS solution is added and reacted for 15-25 min, and then the surface-modified amino group-coated silica gold nanoparticle solution is added and reacted at room temperature for 3-5 h to obtain a solution of gold nanoparticles modified on the surface of silica with silicon dots; the volume ratio of the diluted citric acid modified silicon dot solution, EDC, NHS and surface-modified amino group-coated silica gold nanoparticle solution is 10:1-2:1-2:5-15.

8. The preparation method according to claim 1, characterized in that: In step (7), the gold nanoparticle solution modified on the surface of silicon dioxide and 0.05-0.09 g / mL EDC solution are mixed and reacted for 5-15 min, and then 0.03-0.05 g / mL NHS solution is added and reacted for 15-25 min, and then 0.5-2 mL 3-aminophenylboronic acid is added and reacted for 3-5 h to obtain a plasma enhanced fluorescence fluorescent probe; the volume ratio of the gold nanoparticle solution modified on the surface of silicon dioxide, EDC, NHS and 3-aminophenylboronic acid (3-APBA) is 10:1-3:1-2:5-10.

9. A fluorescent probe of plasmon enhanced fluorescence prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the fluorescent probe according to claim 9 in detecting ellagic acid.